The existential relations in memoirs and autobiographical literature (Eurasian Journal of Philology Science and Education, 2016)
In the article the existential relations in memoirs and autobiographical literature of the 18-th century are considered. In the Russian memoirs and autobiographical literature of the 18-th century there are processes which reflect interaction within the genre of autobiographical memoirs of two types – biographic and social. The biographic type of self-consciousness is characterized by special biographic time. Biographic chronos of this type approves itself and reveals only through an objective support, i.e. the time connected with the destiny of the state, society, concerning the development of the country, fatal decisions. The author’s concept shows installation of the statement of private life: biographic time of non-state life is shown through external fatal historical chronos. In autobiographical compositions of Russians writers of the 18-th century the adventurous-heroic and social approaches cease to exist as objectively independent of the author. They are perceived as two opposites, excluding each other, and appear as the intrinsic basis of the developing concept of the personality and the genre chronotope.
Keywords: memoirs literature; private-chamber consciousness; public appearance; chronotope; autobiographical hero; biographic chronos.